Comparing Online and Offline Learning: Impact on Students' Motivation and Learning Achievement in English Subjects at HSPG Semarang Community Learning Activity Center (Educational Management, 2022)
The aims of this study is to analyze the differences in student motivation and achievement between students who were taught by online learning and students who were taught by offline learning in English subjects at PKBM HSPG Semarang either partially or together. The methodology used in this research is quantitative research. The population in this study were grade C students at PKBM HSPG Semarang, 16 students in total. The sampling technique used by the author is non-probability sampling using saturated sampling. The methods of data collection using questionnaires and documentation. The collected data were analyzed using descriptive test techniques, normality tests, homogeneity tests, correlation tests, and manova tests to test the research hypothesis. The results of this study there were simultaneous significant differences in the average motivation and achievement of students between students who were taught by online learning and students who were taught by offline learning. The effect of online and offline learning on student motivation and achievement is 30.7%. The effect of online and offline learning on student motivation is 16%. The effect of online and offline learning on student achievement is 14.3%. The conclusion of this study is the average motivation and achievement of students taught by offline learning is better than the average motivation and achievement of students taught by online learning.